Transition metal phosphorus sulfide as well as preparation method and application thereof

By preparing and applying transition metal phosphorus sulfide catalysts, the problem of low OER efficiency in hydrogen production in electrolytic water is solved, and high-efficiency electrocatalytic urea oxidation is achieved, which significantly reduces the energy consumption of hydrogen production in electrolytic water production and improves the hydrogen production in electrolytic water production. Energy efficiency.

CN119263231APending Publication Date: 2025-01-07LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411635501.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The oxygen evolution reaction (OER) efficiency of the anode during the electrolytic hydrogen production process is low, resulting in limited overall hydrogen production efficiency. The existing single phosphorus or sulfide catalysts in the urea electrooxidation reaction (UOR) system are not fully used. explore.

Method used

Preparation of transition metal phosphorus sulfides by mixing transition metal, phosphorus and sulfur and sintering in vacuo to form a catalyst with excellent electrocatalytic properties of urea and used it for urea oxidation electrocatalytic electrodes to enhance the electrocatalytic reaction activity.

Benefits of technology

It achieves a more efficient electron transfer and catalytic rate, significantly reduces the energy consumption of the hydrogen production process of water electrolytic, improves the energy efficiency of hydrogen production of water electrolytic, and demonstrates excellent electrocatalytic reaction characteristics and stable electrocatalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263231A_ABST
    Figure CN119263231A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electro-catalysis, in particular to transition metal phosphorus sulfide and a preparation method and application thereof. The invention provides a preparation method of transition metal phosphorus sulfide, which comprises the following steps: mixing transition metal, phosphorus and sulfur to obtain a mixture; and carrying out vacuum sintering on the mixture to obtain the transition metal phosphorus sulfide. According to the preparation method, the transition metal phosphorus sulfide is successfully prepared, the transition metal phosphorus sulfide has excellent urea electro-catalysis performance, and more efficient electro-catalysis urea oxidation can be achieved to assist water electrolysis for hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a transition metal phosphosulfide and a preparation method and application thereof. Background Art

[0002] With the development of social economy, energy and environmental issues have received increasing attention. Hydrogen energy is considered to be one of the ideal clean energy sources in the 21st century due to its high energy density, green and pollution-free, abundant reserves, wide application, and ability to be effectively coupled with clean energy such as wind energy, electricity and solar energy.

[0003] Among many hydrogen production technologies, water electrolysis is regarded as a highly promising renewable energy hydrogen production technology because of its advantages such as high purity of hydrogen and green and pollution-free preparation process. Generally, the process of water electrolysis involves two half-reaction processes, namely the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Both half-reaction processes involve electron transfer. However, the OER process is a multi-step electron transfer process relative to the HER process, which requires a higher potential and exhibits a slower and more difficult reaction, which limits the hydrogen production efficiency of the entire water electrolysis process. Compared with OER, the theoretical reaction potential of urea electrooxidation reaction (UOR) is 0.37V, which is much smaller than the theoretical reaction potential of OER of 1.23V. Therefore, if UOR is used instead of OER at the anode to couple the HER at the cathode, the energy consumption in the water electrolysis reaction can be greatly reduced, thereby improving the energy efficiency of water electrolysis. In addition, urea has the advantages of high energy density and wide sources. Therefore, urea electrooxidation reaction (UOR) coupled with electrocatalytic hydrogen evolution (HER) in the water electrolysis hydrogen production system is regarded as one of the most promising technical strategies for hydrogen production technology.

[0004] Transition metal compounds have gradually shown great practical value and application prospects in the field of electrocatalysis. Among them, transition metal-containing phosphides or sulfides have the characteristics of simple synthesis, low price and excellent catalytic activity, and have the potential to replace precious metal catalysts. There have been some studies on transition metal single sulfide and single phosphide catalysts in the UOR system, and this type of transition metal single phosphorus or sulfide catalyst has shown good electrocatalytic activity. However, transition metal sulfur-phosphorus compound catalysts for the UOR system have been almost not involved. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a transition metal phosphosulfide and a preparation method and application thereof. The preparation method successfully prepares a transition metal phosphosulfide, and the transition metal phosphosulfide has excellent urea electrocatalytic performance and can achieve more efficient electrocatalytic urea oxidation-assisted water electrolysis to produce hydrogen.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a transition metal phosphosulfide, comprising the following steps:

[0008] combining a transition metal, phosphorus, and sulfur to obtain a mixture;

[0009] The mixture is vacuum sintered to obtain the transition metal phosphosulfide.

[0010] Preferably, the transition metal includes titanium, vanadium, chromium, manganese, iron, cobalt, nickel, iridium, ruthenium or molybdenum.

[0011] Preferably, the mass ratio of the transition metal to phosphorus is (2-5):(1-3).

[0012] Preferably, the mass ratio of the transition metal to sulfur is (2-5):(3-10).

[0013] Preferably, the molar ratio of the transition metal, phosphorus and sulfur is 1:1:3.

[0014] Preferably, the mixing method is ball milling;

[0015] The rotation speed of the ball mill is 400-800 r / min, and the time of the ball mill is 20-30 min.

[0016] Preferably, the temperature of the vacuum sintering is 600-800° C., the holding time is 50-70 hours, and the heating rate to the vacuum sintering temperature is 1-5° C. / min.

[0017] The present invention also provides transition metal phosphosulfide prepared by the preparation method described in the above technical solution.

[0018] The present invention also provides the use of the transition metal phosphosulfide described in the above technical solution in the preparation of a urea oxidation electrocatalytic electrode.

[0019] Preferably, the method comprises the following steps:

[0020] Mixing the transition metal phosphosulfide described in the above technical solution with a solvent to obtain a transition metal phosphosulfide ink;

[0021] The transition metal phosphosulfide ink is coated on the surface of a foamed nickel substrate to obtain a urea oxidation electrocatalytic electrode.

[0022] The invention provides a method for preparing a transition metal phosphosulfide, comprising the following steps: mixing a transition metal, phosphorus and sulfur to obtain a mixture; and vacuum sintering the mixture to obtain the transition metal phosphosulfide.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The preparation method of the present invention is easy to operate, has high feasibility, strong practicality, readily available raw materials, is easy to mass produce, and has low cost, and can bring prospects for the development and utilization of the urea oxidation electrocatalyst preparation technology industry;

[0025] At the same time, the transition metal phosphosulfide prepared by the preparation method of the present invention is compared with a single transition metal phosphide or transition metal sulfide, and the synergistic effect of phosphorus and sulfur elements in the transition metal phosphosulfide compound can enable the transition metal phosphosulfide catalyst to produce a better electron distribution near its active site. This optimized and reasonable electron distribution helps the catalyst to achieve more efficient electron transfer, thereby improving the electrocatalytic reaction activity of the catalyst. Therefore, the transition metal sulfide exhibits better electrocatalytic reaction characteristics. In addition, the surface of the transition metal phosphosulfide catalyst can form more types of active sites, and these diverse active sites help to increase the catalytic rate, enhance the electrocatalytic activity, and realize efficient electrocatalytic urea oxidation assisted water electrolysis to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a physical picture of the transition metal phosphosulfide prepared in Example 1;

[0027] Figure 2 is the XRD pattern of the transition metal phosphosulfide described in Example 1;

[0028] Figure 3 is a SEM image of the transition metal phosphosulfide described in Example 1;

[0029] Figure 4 This is a physical picture of the transition metal phosphosulfide ink described in Example 1;

[0030] Figure 5 This is a physical picture of the urea oxidation electrocatalytic electrode described in Example 1;

[0031] Figure 6 The SEM image of the nickel foam substrate (NF) and the urea oxidation electrocatalytic electrode (NiPS3 / NF) described in Example 1;

[0032] Figure 7 Element distribution diagram of NiPS3 / NF described in Example 1;

[0033] Figure 8 The linear sweep voltammetric curves of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode at different current densities described in Example 1;

[0034] Fig. 9The Tafel curves of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system described in Example 1;

[0035] Fig.10 The electrochemical impedance test results of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system described in Example 1;

[0036] Fig.11 The constant current test results of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system described in the examples;

[0037] Fig.12 is the XRD pattern of the transition metal phosphosulfide described in Example 2;

[0038] Fig.13 is a SEM image of the transition metal phosphosulfide described in Example 2;

[0039] Fig.14 The linear sweep voltammetric curves of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode at different current densities described in Example 2;

[0040] Fig.15 The Tafel curves of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system described in Example 2;

[0041] Fig.16 The electrochemical impedance test results of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system described in Example 2;

[0042] Fig.17 These are the constant current test results of the urea oxidation electrocatalytic electrode, nickel foam electrode and commercial Ru-Ir electrode described in Example 2 in the above three-electrode system. DETAILED DESCRIPTION

[0043] The present invention provides a method for preparing a transition metal phosphosulfide, comprising the following steps:

[0044] combining a transition metal, phosphorus, and sulfur to obtain a mixture;

[0045] The mixture is vacuum sintered to obtain the transition metal phosphosulfide.

[0046] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0047] In the present invention, transition metal, phosphorus and sulfur are mixed to obtain a mixture.

[0048] In the present invention, the transition metal, phosphorus and sulfur are preferably solid.

[0049] In the present invention, the transition metal preferably includes titanium, vanadium, chromium, manganese, iron, cobalt, nickel, iridium, ruthenium or molybdenum.

[0050] In the present invention, the mass ratio of the transition metal to phosphorus is preferably (2-5): (1-3), more preferably (2.5-4.5): (1.5-2.5). The mass ratio of the transition metal to sulfur is preferably (2-5): (3-10), more preferably (2.5-4.5): (6-9). The molar ratio of the transition metal, phosphorus and sulfur is preferably 1:1:3. In an embodiment of the present invention, the molar ratio of the transition metal to phosphorus can be 1:1:3.

[0051] In the present invention, the mixing method is preferably ball milling; the rotation speed of the ball milling is preferably 400-800 r / min, more preferably 500-700 r / min, and most preferably 550-650 r / min; the ball milling time is preferably 20-30 min. In an embodiment of the present invention, the ball milling is carried out in a ball mill, the rotation speed of the ball milling can be 600 r / min, and the ball milling time can be 30 min.

[0052] After obtaining the mixture, the present invention performs vacuum sintering on the mixture to obtain the transition metal phosphosulfide.

[0053] In the present invention, the temperature of the vacuum sintering is preferably 600-800°C, more preferably 650-750°C; the holding time of the vacuum sintering is preferably 50-70h, more preferably 55-65h; the heating rate to the temperature of the vacuum sintering is preferably 1-5°C / min, more preferably 2-4°C / min. In an embodiment of the present invention, the temperature of the vacuum sintering can be 700°C, the holding time can be 60h, and the heating rate can be 1°C / min.

[0054] In the present invention, the vacuum sintering process is preferably to put the mixture into a quartz tube with a dent, insert a quartz plug into the dent of the quartz tube, and evacuate the quartz tube with a vacuum pump and a molecular pump respectively until the gas pressure in the tube is lower than 2.5×10 -3 Pa, then, use a high-temperature flame spray gun to heat the position of the quartz plug. When the quartz tube is heated, it shrinks and deforms, so that the quartz tube achieves a sealing effect; then the sealed quartz tube is placed with the bottom facing down and tilted into a programmed temperature muffle furnace for sintering.

[0055] After the vacuum sintering is completed, the present invention preferably includes cooling and ball milling in sequence; the present invention does not have any special limitation on the cooling process, and natural cooling can be performed using a process well known to those skilled in the art. In the present invention, the rotation speed of the ball mill is preferably 400-800r / min, more preferably 500-600r / min; the time of the ball milling is preferably 20-30min, more preferably 23-26min. In an embodiment of the present invention, the ball milling is carried out in a ball mill, the rotation speed of the ball milling can be 600r / min, and the time of the ball milling can be 20min.

[0056] The present invention also provides transition metal phosphosulfide prepared by the preparation method described in the above technical solution.

[0057] The present invention also provides the use of the transition metal phosphosulfide described in the above technical solution in the preparation of a urea oxidation electrocatalytic electrode.

[0058] In the present invention, the application preferably comprises the following steps:

[0059] Mixing the transition metal phosphosulfide described in the above technical solution with a solvent to obtain a transition metal phosphosulfide ink;

[0060] The transition metal phosphosulfide ink is coated on the surface of a foamed nickel substrate to obtain a urea oxidation electrocatalytic electrode.

[0061] The present invention mixes the transition metal phosphosulfide described in the above technical solution with a solvent to obtain a transition metal phosphosulfide ink.

[0062] In the present invention, the solvent preferably includes deionized water, ethanol and commercial Nafion solution in a volume ratio of 1:1:0.05.

[0063] In the present invention, the ratio of the mass of the transition metal phosphosulfide to the volume of the solvent is preferably 100 mg:2.05 μL.

[0064] In the present invention, the mixing is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 2 to 3 hours. The present invention has no special limitation on the frequency of the ultrasound, and the frequency well known to those skilled in the art can be used.

[0065] After obtaining the transition metal phosphosulfide ink, the present invention coats the transition metal phosphosulfide ink on the surface of a foam nickel substrate to obtain a urea oxidation electrocatalytic electrode.

[0066] In the present invention, the coating method is preferably drop coating. The present invention has no special limitation on the drop coating process, and the process well known to those skilled in the art can be used. In the present invention, the coating amount is preferably 10 to 20 mg / cm 2 , more preferably 10 mg / cm 2 .

[0067] After the coating is completed, the present invention also preferably includes drying; the drying temperature is preferably 60-80°C, more preferably 65-75°C, most preferably 68-72°C; the drying time is preferably 2-3h, more preferably 2.3-2.6h.

[0068] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0069] Example 1

[0070] 50 g of nickel solid element (0.852 mol), 26.41 g of phosphorus solid element (0.853 mol) and 81.77 g of sulfur solid element (2.550 mol) were mixed and put into a ball mill, and ball milled at 600 r / min for 30 min to obtain a mixture;

[0071] The mixture was placed in a quartz tube with a dent, a quartz plug was inserted into the dent of the quartz tube, and the quartz tube was evacuated by a vacuum pump and a molecular pump successively until the pressure in the tube was lower than 2.5×10 -3 After Pa, the position of the quartz plug is heated with a high-temperature flame spray gun. When the quartz tube is heated, it shrinks and deforms, so that the tube achieves a sealing effect. Then, the tube is placed bottom-down and tilted into a muffle furnace for sintering. The sintering process is as follows: heating from room temperature to 700°C at a heating rate of 1°C / min, and then keeping warm for 60 hours; after the sintering is completed, it is cooled with the furnace, the quartz tube is opened, the vacuum sintered product is taken out, and then it is put into a ball mill again at 600r / min for 20 minutes to obtain a transition metal phosphosulfide (NiPS3, as shown in the actual picture Figure 1 shown);

[0072] Figure 2 is the XRD pattern of the transition metal phosphosulfide, Figure 2 It can be seen that NiPS3 was successfully prepared by high-temperature solid-phase reaction method;

[0073] Figure 3 is the SEM image of the transition metal phosphosulfide, Figure 3 Combination Figure 2 This further proves that NiPS3 was successfully prepared.

[0074] 10 mg of the transition metal phosphosulfide, 100 μL of deionized water, 100 μL of ethanol and 5 μL of commercial Nafion solution (Alfa Aesar, Nafion D-520 dispersion, CAS: 31175-20-9) were mixed and ultrasonicated at room temperature for 2 h to obtain a transition metal phosphosulfide ink (see the actual picture). Figure 4 shown);

[0075] By drop coating, 0.2 mL of the transition metal phosphosulfide ink was applied to the surface of the nickel foam substrate (the size of the nickel foam substrate was 1×2 cm, and the coating area was 1×1 cm), and then dried at 70°C for 2 h to obtain a 10 mg / cm -2 Catalyst urea oxidation electrocatalytic electrode (actual picture as shown Figure 5 shown);

[0076] The nickel foam substrate (NF) and the urea oxidation electrocatalytic electrode (NiPS3 / NF) were subjected to SEM testing, and the test results are as follows: Figure 6 As shown by Figure 6 It can be seen that compared with the surface of NF, the surface of NiPS3 / NF is covered with a uniform transition metal phosphosulfide coating, which indicates that the transition metal phosphosulfide is effectively loaded on the nickel foam substrate, which will greatly increase the active area of ​​the catalytic electrode;

[0077] Figure 7 is the element distribution diagram of the NiPS3 / NF, Figure 7 It can be seen that the nickel, phosphorus and sulfur elements in the transition metal phosphosulfide (NiPS3) are uniformly distributed, which further confirms that NiPS3 is uniformly loaded on the nickel foam substrate;

[0078] The urea oxidation electrocatalytic electrode, nickel foam electrode and commercial Ru-Ir electrode were evaluated and tested for urea oxidation electrocatalytic performance in a three-electrode system: the electrochemical tests were carried out in a 1 mol / L potassium hydroxide solution and a mixed solution of 1 mol / L potassium hydroxide and 0.33 mol / L urea, respectively. OER occurred in the former electrochemical test and UOR occurred in the latter electrochemical test. In order to prove that the urea oxidation electrocatalytic electrode has excellent UOR performance, UOR and OER electrochemical tests were carried out using a commercial Ru-Ir precious metal electrode for comparison. At the same time, in order to avoid interference from the NF substrate, a UOR electrochemical test comparison of NF was also carried out; Figure 8is the linear sweep voltammetric curve of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode at different current densities, Figure 8 It can be seen that at 10mA / cm -2 At a current density of 100 mA / cm, the UOR potential of the urea oxidation electrocatalytic electrode is 1.384 V, which is significantly lower than the potentials of the Ru-Ir commercial electrode for OER (potential of 1.513 V) and UOR (potential of 1.587 V). -2 Under the conditions of , the potential of UOR of the urea oxidation electrocatalytic electrode is only 1.476V, which is significantly lower than the OER (potential of 1.625V) and UOR (potential of 1.772V) of the Ru-Ir electrode. It can be seen that the UOR produced by NiPS3 / NF not only effectively reduces the high energy consumption required for OER in traditional water electrolysis hydrogen production, but also shows excellent UOR catalytic performance compared with commercial precious metal electrodes;

[0079] Fig. 9 is the Tafel curve of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system, Fig. 9 It can be seen that since the Tafel slope can reflect the change in the electrocatalytic reaction rate on the electrode, the smaller the Tafel slope, the better the oxygen evolution reaction kinetic characteristics of the electrode. The Tafel curve test results of NF-UOR, NiPS3 / NF-UOR, Ru-Ir-UOR, and Ru-Ir-OER show that the Tafel slope of NiPS3 / NF-UOR is 43.74mV / dec, which is significantly lower than 258.71mV / dec of NF-UOR, 106.71mV / dec of Ru-Ir-OER, and 158.80mV / dec of Ru-Ir-UOR; therefore, the NiPS3 / NF-UOR exhibits more excellent kinetic characteristics;

[0080] Fig.10 The electrochemical impedance test results of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system are as follows; Fig.10 It can be seen that in the electrochemical impedance spectroscopy (EIS) test, R ct Represents the charge transfer of electrochemical reactions, R ct The smaller the value, the faster the charge transfer rate during the electrochemical reaction and the better the electrochemical performance of the catalyst. The EIS test results show that the R ct The R of Ru-Ir-OER is 17806Ω. ct The R of Ru-Ir-UOR is 2066Ω ctis 3440Ω, while the R ct It is only 813.6Ω; therefore, NiPS3 / NF-UOR exhibits better electrochemical activity;

[0081] Fig.11 The constant current test results (potential change and electrochemical stability under constant current) of the urea oxidation electrocatalytic electrode, nickel foam electrode and commercial Ru-Ir electrode in the above three-electrode system are shown in FIG. Fig.11 It can be seen that the potential of NiPS3 / NF-UOR remained stable at around 1.4 V within 24 hours, while the potential of NF-UOR fluctuated greatly and rose to around 1.85 V. The potential of Ru-Ir-OER showed an upward trend between 1.55 V and 1.6 V, and the potential of Ru-Ir-UOR also showed an obvious upward trend between 1.7 V and 1.8 V. Obviously, NiPS3 / NF-UOR has a lower potential and more stable electrocatalytic activity under the same current density.

[0082] Example 2

[0083] 50 g of solid iron (0.89 mol), 27.68 g of solid phosphorus (0.89 mol) and 85.71 g of solid sulfur (2.673 mol) were mixed and put into a ball mill, and ball-milled at 600 r / min for 30 min to obtain a mixture;

[0084] The mixture was placed in a quartz tube with a dent, a quartz plug was inserted into the dent of the quartz tube, and the quartz tube was evacuated by a vacuum pump and a molecular pump successively until the pressure in the tube was lower than 2.5×10 -3 After Pa, the position of the quartz plug is heated with a high-temperature flame spray gun. When the quartz tube is heated, it will shrink and deform, so that the tube achieves a sealing effect. Then, the tube is placed bottom down and tilted into a muffle furnace for sintering. The sintering process is: heating from room temperature to 700°C at a heating rate of 1°C / min, and keeping warm for 60 hours; after the sintering is completed, it is cooled with the furnace, the quartz tube is opened, the vacuum sintered product is taken out, and it is put into the ball mill again at 600r / min for 20 minutes to obtain a transition metal phosphosulfide (FePS3);

[0085] Fig.12 is the XRD pattern of the transition metal phosphosulfide, Fig.12 It can be seen that FePS3 was successfully prepared by high-temperature solid-phase reaction method;

[0086] Fig.13 is the SEM image of the transition metal phosphosulfide, Figure 3It can be seen that the transition metal phosphosulfide presents a two-dimensional layered structure, which is consistent with the morphological characteristics of transition metal phosphosulfide, which further proves that FePS3 has been successfully prepared.

[0087] 10 mg of the transition metal phosphosulfide, 100 μL of deionized water, 100 μL of ethanol and 5 μL of commercial Nafion solution were mixed, and ultrasonicated at room temperature for 2 h to obtain a transition metal phosphosulfide ink;

[0088] By drop coating, 0.2 mL of the transition metal phosphosulfide ink was applied to the surface of the nickel foam substrate (the size of the nickel foam substrate was 1×2 cm, and the coating area was 1×1 cm), and then dried at 70°C for 2 h to obtain a 10 mg / cm -2 Catalyst for urea oxidation electrocatalytic electrode;

[0089] The urea oxidation electrocatalytic electrode (FePS3 / NF), nickel foam electrode (NF) and commercial Ru-Ir electrode were evaluated and tested for their urea oxidation electrocatalytic performance in a three-electrode system: the electrochemical tests were conducted in a 1 mol / L potassium hydroxide solution and a mixed solution of 1 mol / L potassium hydroxide and 0.33 mol / L urea, respectively. OER occurred in the former electrochemical test, and UOR occurred in the latter electrochemical test. In order to prove that the urea oxidation electrocatalytic electrode has excellent UOR performance, UOR and OER electrochemical tests were performed and compared using a commercial Ru-Ir precious metal electrode. At the same time, in order to avoid interference from the NF substrate, a UOR electrochemical test comparison of NF was also performed; Fig.14 is the linear sweep voltammetric curve of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode at different current densities, Fig.14 It can be seen that at 10mA / cm -2 At a current density of 100 mA / cm, the UOR potential of the urea oxidation electrocatalytic electrode is 1.389 V, which is significantly lower than the potentials of the Ru-Ir commercial electrode for OER (potential of 1.513 V) and UOR (potential of 1.587 V). -2 Under the conditions of , the potential of UOR of the urea oxidation electrocatalytic electrode is only 1.515V, which is significantly lower than the OER (potential of 1.625V) and UOR (potential of 1.772V) of the Ru-Ir electrode. It can be seen that the UOR produced by FePS3 / NF not only effectively reduces the high energy consumption required for OER in traditional water electrolysis hydrogen production, but also exhibits excellent UOR catalytic performance compared to commercial precious metal electrodes;

[0090] Fig.15is the Tafel curve of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system, Fig.15 It can be seen that since the Tafel slope can reflect the change in the electrocatalytic reaction rate on the electrode, the smaller the Tafel slope, the better the oxygen evolution reaction kinetic characteristics of the electrode. The Tafel curve test results of NF-UOR, NiPS3 / NF-UOR, Ru-Ir-UOR, and Ru-Ir-OER show that the Tafel slope of FePS3 / NF-UOR is 72.72mV / dec, which is significantly lower than 258.71mV / dec of NF-UOR, 106.71mV / dec of Ru-Ir-OER, and 158.80mV / dec of Ru-Ir-UOR; therefore, the FePS3 / NF-UOR exhibits more excellent kinetic characteristics;

[0091] Fig.16 The electrochemical impedance test results of the urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode in the above three-electrode system are as follows; Fig.16 It can be seen that in the electrochemical impedance spectroscopy (EIS) test, R ct Represents the charge transfer of electrochemical reactions, R ct The smaller the value, the faster the charge transfer rate during the electrochemical reaction and the better the electrochemical performance of the catalyst. The EIS test results show that the R ct The R of Ru-Ir-OER is 17806Ω. ct The R of Ru-Ir-UOR is 2066Ω ct is 3440Ω, while the R ct It is only 189.1Ω; therefore, FePS3 / NF-UOR exhibits better electrochemical activity;

[0092] Fig.17 The urea oxidation electrocatalytic electrode, the nickel foam electrode and the commercial Ru-Ir electrode were subjected to constant current testing (potential change and electrochemical stability under constant current) in the above three-electrode system. Fig.17 It can be seen that the potential of FePS3 / NF-UOR remained stable at around 1.45 V within 24 hours, while the potential of NF-UOR fluctuated greatly and rose to around 1.85 V. The potential of Ru-Ir-OER showed an upward trend between 1.55 V and 1.6 V, and the potential of Ru-Ir-UOR also showed an obvious upward trend between 1.7 V and 1.8 V. Obviously, FePS3 / NF-UOR has a lower potential and more stable electrocatalytic activity under the same current density conditions.

[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a transition metal phosphosulfide, characterized in that: The following steps are involved: combining a transition metal, phosphorus, and sulfur to obtain a mixture; The mixture is vacuum sintered to obtain the transition metal phosphosulfide.

2. The preparation method according to claim 1, characterized in that The transition metal includes titanium, vanadium, chromium, manganese, iron, cobalt, nickel, iridium, ruthenium or molybdenum.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the transition metal to phosphorus is (2-5):(1-3).

4. The preparation method according to claim 3, characterized in that: The mass ratio of the transition metal to sulfur is (2-5):(3-10).

5. The preparation method according to claim 4, characterized in that: The molar ratio of the transition metal, phosphorus and sulfur is 1:1:

3.

6. The preparation method according to claim 5, characterized in that: The mixing method is ball milling; The rotation speed of the ball mill is 400-800 r / min, and the time of the ball mill is 20-30 min.

7. The preparation method according to any one of claims 1 or 4 to 6, characterized in that: The vacuum sintering temperature is 600-800° C., the heat preservation time is 50-70 hours, and the heating rate to the vacuum sintering temperature is 1-5° C. / min.

8. The transition metal phosphosulfide prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the transition metal phosphosulfide according to claim 8 in preparing a urea oxidation electrocatalytic electrode.

10. The use according to claim 9, characterized in that The following steps are involved: Mixing the transition metal phosphosulfide of claim 9 with a solvent to obtain a transition metal phosphosulfide ink; The transition metal phosphosulfide ink is coated on the surface of a foamed nickel substrate to obtain a urea oxidation electrocatalytic electrode.

Citation Information

Cited By

  • Preparation method and application of transition metal phosphorus sulfide with two-dimensional nano layered structure

    CN121097103A